Cover Image. (7th May 2018) - Lin, J.; Weng, Y.; Li, M.; Mo, Y.; Zhao, J.
Abstract : The cover image, by JiXian Lin et al., is based on the Original Article Hydration prevents chronic hyperglycaemic patients from neurological deterioration post‐ischaemic stroke, DOI:10.1111/ane.12900 . Design credit: Qingmei Zhang.